Integration of energy storage in distribution grids - Geth, Frederik; Tant, Jeroen; Haesen, Edwin; Driesen, Johan; Belmans, Ronnie (IEEE PES General Meeting, 2010)
Electrical energy storage services can bring benefit to multiple stakeholders in the distribution grid. Energy storage owners maximize their profit on an external energy market. This can cause a conflict with the distribution system operator because a grid is designed in terms of peak power, not energy. The subject of this paper is a optimization method for the siting and sizing of energy storage in distribution grids. The optimization is implemented multi-objective as to visualize the trade-offs between storage stakeholders and distribution system operators.